Analysis of GaN MagHEMTs - Petar Igic (Semiconductor Science and Technology, 2018)
The simulations, calibration, measured output currents and relative sensitivity of the first-ever fabricated gallium nitride (GaN) magnetic high electron mobility transistors (MagHEMTs) are given in this work. The current imbalance and relative sensitivities obtained from simulations are calibrated against the experimental data measured at room temperature (RT). The average calculated relative sensitivity of the 60 fabricated devices measured is 11.98%T−1. We present three-dimensional simulation results of GaN split-current magnetic sensors for different geometrical and biasing parameters at various ambient temperatures. The detailed analysis of device behaviour is given for each scenario. The relative sensitivity degrades at 400 K (S r = 6.78%T−1) and 500 K (S r = 4.91%T−1) compared to the sensitivity measured at 300 K (S r = 11.98%T−1). The GaN MagHEMTs show promising predicted relative sensitivities at 400 K and 500 K compared to silicon magnetic field effect transistors (MagFETs) operating at much lower temperatures. Moreover, device geometrical parameters are optimised to enhance the relative sensitivity from 11.98%T−1 to 23.29%T−1 using the commercial simulation toolbox Atlas, by Silvaco.